Augmented Reality (AR) concept in hospitality education: advantages and challenges / Ahmad Hidayat Ahmad Ridzuan, Norfezah Md Nor and Nur'Hidayah Che Ahmat - Ahmad Ridzuan, Ahmad Hidayat; Md Nor, Norfezah; Che Ahmat, Nur Hidayah (UiTM Press, 2020)
The Augmented Reality (AR) Concept in education is mostly studied and applied in the areas of mathematics education, science educations and educational technology. While in the tourism industry, it's played an important role as a marketing tools towards smart tourism approach. However, the Augmented Reality (AR) Concept in hospitality education have not yet been explored. Thus, this study aims to review existing literature to identify advantages and challenges pertaining to Augmented Reality (AR) Concept in the hospitality education. The output may give new perspective and potential application that may enhance the learning achievement and the hospitality course may become more interesting. Moreover. this may help the education provider towards movement to the Fourth Industrial Revolution 4.0 (IR 4.0) demand.